2016
DOI: 10.1097/rmr.0000000000000077
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Plasticity in the Setting of Brain Tumors

Abstract: Cortical reorganization of function due to the growth of an adjacent brain tumor has clearly been demonstrated in a number of surgically proven cases. Such cases demonstrate the unmistakable implications for the neurosurgical treatment of brain tumors, as the cortical function may not reside where one may initially suspect based solely on the anatomical magnetic resonance imaging (MRI). Consequently, preoperative localization of eloquent areas adjacent to a brain tumor is necessary, as this may demonstrate une… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 32 publications
1
26
0
2
Order By: Relevance
“…Neuroplasticity is the ability of the brain to reorganize itself during normal development and in response to illness; it has been extensively reported in normal adult humans, ischemic stroke patients, and brain injury patients (Kong et al, 2016). In glioma patients, increasing studies have demonstrated that both ipsilateral and contralateral brain regions are recruited to compensate for the neurological dysfunction caused by glioma-induced injury Krieg et al, 2013;Auriat et al, 2015;Fisicaro et al, 2016). To date, no study has detected whether the structural and functional plasticity of contralesional MTL in patients with unilateral MTL glioma exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroplasticity is the ability of the brain to reorganize itself during normal development and in response to illness; it has been extensively reported in normal adult humans, ischemic stroke patients, and brain injury patients (Kong et al, 2016). In glioma patients, increasing studies have demonstrated that both ipsilateral and contralateral brain regions are recruited to compensate for the neurological dysfunction caused by glioma-induced injury Krieg et al, 2013;Auriat et al, 2015;Fisicaro et al, 2016). To date, no study has detected whether the structural and functional plasticity of contralesional MTL in patients with unilateral MTL glioma exist.…”
Section: Discussionmentioning
confidence: 99%
“…This property, known as neuroplasticity, has been demonstrated extensively in many brain regions by functional and structural magnetic resonance imaging (MRI) in the past two decades. In terms of brain lesions, including those resulting from brain injuries, strokes, and brain tumors, functional imaging studies have identified the brain to maintain its original features or to support functional recovery by recruiting other parts of the brain, such as the perilesional brain, contralesional brain, and homologous function of the brain, in order to compensate for lost functions (Small et al, 2002;Freundlieb et al, 2015;Fisicaro et al, 2016;Han et al, 2017Han et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral plasticity is the biological dynamic ability of the central nervous system to reorganize itself in response to injuries, such as damages caused by brain tumors [1, 2]. The reorganization of functional areas is a fundamental mechanism to compensate for impaired function [3].…”
Section: Introductionmentioning
confidence: 99%
“…While traditional MR imaging can accurately identify the anatomic relationship of critical brain regions with AVMs, it does not provide information regarding functional connectivity, and it fails to account for the plasticity of brain function that has been shown to occur in the context of underlying brain lesions or injury (22,23). AVM proximity to eloquent cortex, in addition to nidus size and venous drainage, is a major contributing factor to patient morbidity and postoperative neurologic decline (23).…”
Section: Discussionmentioning
confidence: 99%